(untitled) - Moritani, Masanori (Japan, 1983)
This book introduces about Japanese technology in perspective, Japanese technology in time of strained international relations, Japan as provider of technology, Japan and future technology.
Keywords: Japan,Nhật Bản; Technology,Công nghệ